2021
DOI: 10.3390/en14061715
|View full text |Cite
|
Sign up to set email alerts
|

Extended SINDICOMP: Characterizing MV Voltage Transformers with Sine Waves

Abstract: The paper presents a method for the frequency characterization of voltage transformers (VTs) for medium voltage (MV) grids which involves only sine waves. It is called extended SINDICOMP, since it is an extended version of the previously developed technique SINDICOMP. It requires, in the first step, an evaluation and a compensation of the non-linearity introduced by the VT when it is supplied with a 50 Hz sinusoidal input at rated value. Then, the VT is characterized with a low voltage sinusoidal frequency swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…At present, there are few papers in the literature dealing with metrological performances of ITs used for PQ measurement. Some authors of this paper have already shown that the metrological performances of ITs in the presence of PQ phenomena can drastically change [ 30 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Analysis Of the Literature And Standards Regarding Its And P...mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are few papers in the literature dealing with metrological performances of ITs used for PQ measurement. Some authors of this paper have already shown that the metrological performances of ITs in the presence of PQ phenomena can drastically change [ 30 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Analysis Of the Literature And Standards Regarding Its And P...mentioning
confidence: 99%
“… The test waveform should be complex because the error of ITs can be drastically increased when more PQ phenomena are superimposed to fundamental waveform. The simple and consolidated compensation techniques [ 33 , 34 , 35 ] present in the literature are ineffective when several PQ phenomena are superimposed to fundamental waveform. …”
Section: Analysis Of the Literature And Standards Regarding Its And P...mentioning
confidence: 99%
“…In fact, [4]- [7] propose techniques to measure and compensate the IT non-linearity, leading to a strong reduction of the IT errors contribution in harmonic measurement. In particular, in [4] and [5], the nonlinearities are measured and compensated by measuring the spurious phasors at the IT secondary side when it is supplied with a sinusoidal signal at rated voltage and frequency. In [6] and [7], the compensating phasors are measured suppling a VT with dual-tone and multitone signals, respectively.…”
Section: B Verification Of It Performance In Pq Measurementsmentioning
confidence: 99%
“…In this paper the determined characteristic of voltage ratio error at harmonics with frequency for a given medium voltage inductive instrument transformer is used to predict the value of the slow-front overvoltage in its secondary circuit. The nonlinearity of the magnetization characteristics of the magnetic core of the inductive VTs causes the need for accurate evaluation of the values of ratio error and phase displacement at harmonics of the rated primary voltage; this is required during the test [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. There are many methods and measuring systems that enable evaluation of the values of ratio error at harmonics of inductive VT.…”
Section: Introductionmentioning
confidence: 99%
“…There are many methods and measuring systems that enable evaluation of the values of ratio error at harmonics of inductive VT. The most recent solutions from a given group of authors are referenced as [ 17 , 18 , 25 ]. However, the resonance frequencies and the measured values of ratio error and phase displacement do not change with the value of the applied voltage.…”
Section: Introductionmentioning
confidence: 99%